The Influence of Affiliate Marketing, Content Marketing, and Product Uniqueness on Purchase Decisions in Fashion TikTok Shops in the Digital Era - Aprilia Galih Raka Siwi; Kussudyarsana (Faculty of Economics and Business, University of Pancasakti Tegal, 2024)
This scholarly investigation aimed to explore the effects of affiliate marketing, content marketing, and product distinctiveness on the purchasing behaviors of TikTok Shop users in the fashion sector. A quantitative research design was utilized, incorporating a carefully crafted questionnaire that was administered to a cohort of 160 individuals who met specified inclusion criteria. The acquired data were analyzed through multiple linear regression methodologies to determine both the separate and combined impacts of the three independent variables. The results demonstrated that all three variables had a positive and statistically significant impact on purchasing decisions, with product distinctiveness showing the most substantial effect. The regression analysis indicated that 55.5% of the variance in purchasing decisions could be explained by these variables. Despite its meaningful contributions, the study is limited by its small sample size, regional constraints, and the exclusion of other potentially significant factors, such as pricing strategies, brand loyalty, and perceived consumer value. This research contributes to the existing literature by integrating the three marketing variables within the context of short-form video-driven e-commerce and provides practical insights for marketers seeking to enhance consumer engagement and boost sales performance on TikTok Shop.